Changes in sprint and jump performances after traditional, plyometric, and combined resistance training in male youth pre- and post-peak height velocity - Lloyd, R. S.; Radnor, J. M.; De Ste Croix, M. B. A.; Cronin, J. B.; Oliver, J. L. (The Journal of Strength and Conditioning Research, 2016)
The purpose of this study was to compare the effectiveness of 6-week training interventions using different modes of resistance (traditional strength, plyometric, and combined training) on sprinting and jumping performances in boys before and after peak height velocity (PHV). Eighty school-aged boys were categorized into 2 maturity groups (pre- or post-PHV) and then randomly assigned to (a) plyometric training, (b) traditional strength training, (c) combined training, or (d) a control group. Experimental groups participated in twice-weekly training programs for 6 weeks. Acceleration, maximal running velocity, squat jump height, and reactive strength index data were collected pre- and postintervention. All training groups made significant gains in measures of sprinting and jumping irrespective of the mode of resistance training and maturity. Plyometric training elicited the greatest gains across all performance variables in pre-PHV children, whereas combined training was the most effective in eliciting change in all performance variables for the post-PHV cohort. Statistical analysis indicated that plyometric training produced greater changes in squat jump and acceleration performances in the pre-PHV group compared with the post-PHV cohort. All other training responses between pre- and post-PHV cohorts were not significant and not clinically meaningful. The study indicates that plyometric training might be more effective in eliciting short-term gains in jumping and sprinting in boys who are pre-PHV, whereas those who are post-PHV may benefit from the additive stimulus of combined training.